2018
DOI: 10.1093/jjco/hyy179
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib versus standard-of-care EGFR-TKI as first-line treatment for EGFRm advanced NSCLC: FLAURA Japanese subset

Abstract: In the FLAURA trial Japanese subset, osimertinib significantly improved median PFS versus standard-of-care (gefitinib) in patients with previously untreated EGFR (exon 19 deletion or L858R) mutation-positive advanced or metastatic NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
108
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 22 publications
8
108
2
2
Order By: Relevance
“…There is a significant difference in the composition ratio of patients with multiple CNS metastases in each group, possibly resulting from variability in the response to the EGFR-TKI in diverse reports [19,29]. In the present study, the survival benefits of OSI over AFA were consistent with prospective randomized trials [22,25,30,31]in which the composition ratio of multiple CNS metastases was assessed in subgroup analyses. Consequently, the betweengroup differences in survival benefits might be attributed to drug mechanistic differences [22,32].…”
Section: Discussionsupporting
confidence: 82%
“…There is a significant difference in the composition ratio of patients with multiple CNS metastases in each group, possibly resulting from variability in the response to the EGFR-TKI in diverse reports [19,29]. In the present study, the survival benefits of OSI over AFA were consistent with prospective randomized trials [22,25,30,31]in which the composition ratio of multiple CNS metastases was assessed in subgroup analyses. Consequently, the betweengroup differences in survival benefits might be attributed to drug mechanistic differences [22,32].…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, third-generation EGFR-TKIs have been designed to inhibit mutated EGFR and are rarely associated with dermatologic AEs. Although ethnic differences in skin toxicities have not been observed in phase III trials of first-, second-and third-generation EGFR-TKIs, Japanese patients tend to develop a rash more frequently compared to their global, European and non-Japanese Asian counterparts [5,13,14]. However, only a few SJS/TEN cases associated with EGFR-TKIs have been reported [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Japanese subset of the FLAURA study population had a higher frequency of pulmonary disorders (all grades: 12%, Grade 3 or higher: 2%); it should be noted that this is a first-line trial. Other reports have also suggested that osimertinib may be associated with an increased incidence of pulmonary disorders relative to other EGFR-TKIs [32]. Nevertheless, the odds ratio for pulmonary disorders after gefitinib treatment was 1.92-fold higher among Japanese patients who were ≥55 years old, which suggests that careful follow-up is required for patients who are ≥75 years old [35].…”
Section: Discussionmentioning
confidence: 94%
“…Osimertinib has also been reported to be more frequently myelosuppressed than in other EGFR-TKI in a pivotal study [13,14]. In addition, myelosuppression was reported to be stronger in the analysis of the Japanese population [32]. Although the obvious mechanism was unclear, it was suggested that racial differences might be involved.…”
Section: Discussionmentioning
confidence: 99%